HIV/AIDS em jovens de Santarém - Pará entre os anos de 2012 e 2022 - SILVA, Thalita Maia da (Universidade Federal do Oeste do Pará, 2024)
The Acquired Immunodeficiency Syndrome (AIDS) is considered a current pandemic and in Brazil the most vulnerable group to the virus are young people between 20 and 59 years old (SOUZA et al., 2013). The presence of the disease in the body cancels the natural defense mechanisms of the human body, easily allowing contamination by other diseases. Despite the dissemination of data on the disease at the national level, little is discussed about the occurrence in Brazilian regions and states. Thus, this study aimed to analyze the occurrence of HIV/AIDS cases in young people from Santarém - Pará, between the years 2012 and 2022. The research was carried out through an epidemiological study, with quantitative and descriptive data, with an exploratory character, collected in two ways, the first, through the National Medical Assistance System (SINAM), in the SUS Information Department (DATASUS) , through the Pará State Health Department (SESPA), to obtain the occurrence of HIV/AIDS cases among young people in the municipality of Santarém in the last ten years and to characterize and compare the profile of infected young people, by sex and age group. For the second form of data collection, an Integrative Literature Review (RIL) was carried out to identify the health vulnerabilities of those affected, through studies carried out in Brazil in the last 10 years. In Santarém, between the years 2012 to 2022, the time period with the highest occurrence of cases was the years 2017 and 2018. Regarding the age of the young people surveyed, the age group from 15 to 29 years old was used and within In this age group, the largest number of HIV cases are young males, aged 20 to 24 years, who declare themselves brown. And as for the profile of the reviewed materials, of the 23 articles studied, only two are from the North region. As for the evidence identified in the RIL, the study revealed three groups of vulnerabilities experienced by young people with regard to HIV, individual, social and programmatic vulnerabilities. Within the scope of Individual vulnerability, aspects such as: Unprotected sexual intercourse, drug use and incorrect or insufficient knowledge about the disease were identified. In Social vulnerability, racial and socioeconomic inequality and low education were found. Finally, in the programmatic vulnerability, lack of information availability, inequality in access and accessibility to health services, fragility in prevention actions and implementation of public policies were identified. The study brought the reflection that the profile of young people affected by HIV/AIDS in Santarém - Pará, may be being impacted by the vulnerabilities that the group experiences, which is not restricted to behavioral and individual issues, it comes up against aspects of a political and that need to be discussed between the Municipal and State Health Departments, the Pará State Department of Education and the local Universities, regarding the need to foster collective dialogue on policies for the promotion and prevention of Sexually Transmitted Infections that serve young people in different contexts of sexual and cultural diversity and socioeconomic inequality.